Boris Johnson: the moral case for government resignations in July 2022 - Walker, R (Palgrave Macmillan, 2022)
Although comparatively rare, political resignations are essential for the health of democracy and political institutions. Protagonists risk their political careers when resigning but can hold governments to account and make real the Nolan principles of public life. In July 2022, an unprecedented 62 resignations ended Boris Johnson’s time as British prime minister to be replaced first by Liz Truss and then, 44 days later, by Rishi Sunak, the second minister to resign. An inductive, qualitative, content analysis of the resignation letters elucidates the reasons for the resignations and highlights the ethical dilemmas that confronted would be resignees. Events lessened the effectiveness of government, triggered fears for the electoral prospects of the Conservative Party and separately challenged individuals’ personal integrity. Considerations that prevented resignees acting earlier—promises that things would change, competing loyalties, fear of reprisal, love of job, attachment to status and allegiance to ideological faction—may partially explain why much of government remained in post in July.